The Influence of Principal’s Empowerment on the Work Performance of the Committee Head: Pengaruh pengupayaan Pengetua terhadap prestasi kerja Ketua Panitia - Murad, Maziana binti; Yunus, Jamal @ Nordin bin; Mohd Noor, Nor Aini binti (Management Research Journal, 2022)
Empowerment refers to giving autonomy to teachers to be involved in a plan in the school to be more committed and dedicated to the tasks entrusted to them. The purpose of this study is to examine the influence of empowerment on the work performance of the head of the Sijil Pelajaran Malaysia (SPM) subject committee in secondary schools. The study also describes a measurement model and a structural model of enabling job performance. This survey study involved 278 committee heads in selected secondary schools in the state of Pahang. The research instrument used in this study was adapted from the Empowerment Indicator Survey and Work Performance developed by Supian and Khadijah (2012). Data were analyzed using SPSS and SmartPLS 3.0 applications. The results showed that the values ​​of R2 were 0.192, f2 (0.238) and Q2 (0.050). Overall, the results of the analysis showed that there was a significant positive relationship between the influence of principal empowerment with job performance (β = 0.438, t = 8.698, p <0.05). As this study only involves the head of the committee in secondary schools in the state of Pahang, then the results of this study are limited to be generalized and can not give an overall picture of the population of the head of the committee throughout the country. Therefore, it is recommended that this study be conducted in secondary schools throughout the country by taking into account the culture and type of leadership of principals.